Dysfunctional BCAA degradation triggers neuronal damage through disrupted AMPK-mitochondrial axis due to enhanced PP2Ac interaction - Shih-Cheng Wu; Yan-Jhen Chen; Shih-Han Su; Pai-Hsiang Fang; Rei-Wen Liu; Hui-Ying Tsai; Yen-Jui Chang; Hsing-Han Li; Jian-Chiuan Li; Chun-Hong Chen (Communications Biology)
Abstract Metabolic and neurological disorders commonly display dysfunctional branched-chain amino acid (BCAA) metabolism, though it is poorly understood how this leads to neurological damage. We investigated this by generating Drosophila mutants lacking BCAA-catabolic activity, resulting in elevated BCAA levels and neurological dysfunction, mimicking disease-relevant symptoms. Our findings reveal a reduction in neuronal AMP-activated protein kinase (AMPK) activity, which disrupts autophagy in mutant brain tissues, linking BCAA imbalance to brain dysfunction. Mechanistically, we show that excess BCAA-induced mitochondrial reactive oxygen species (ROS) triggered the binding of protein phosphatase 2 A catalytic subunit (PP2Ac) to AMPK, suppressing AMPK activity. This initiated a dysregulated feedback loop of AMPK-mitochondrial interactions, exacerbating mitochondrial dysfunction and oxidative neuronal damage. Our study identifies BCAA imbalance as a critical driver of neuronal damage through AMPK suppression and autophagy dysfunction, offering insights into metabolic-neuronal interactions in neurological diseases and potential therapeutic targets for BCAA-related neurological conditions.